Studi Numerik Penambahan Pelat Pengaku Diagonal Pada Steel Plate Shear Wall (SPSW) dengan Adanya Variasi Opening - Novin Agustina Nur Putri (Jurnal Aplikasi Teknik Sipil, 2021)
Steel Plate Shear Wall (SPSW) is an earthquake-resistant structural system. SPSW is applied to high rise buildings. The application of SPSW in high rise buildings allows for an opening for the architectural needs of the building, but the modeling of the opening can affect the performance of the structure. In this study, validation was carried out using the Abaqus aid program related to the shear force achievement parameters and the hysteresis curve of the experimental model SPSW (S4) which has a circular opening in the middle of the span. In the results of the validation of the SPSW (S4) model using Abaqus, the maximum shear force achieved is 710 kN at a drift of 4.11%, while the experimental Alavi conducted 740 in at a drift of 3.80%. The results of the maximum shear force between modeling using Abaqus and Experimental conducted by Alavi are not much different, with value 4.05%. Then the SPSW model was applied by opening the box in the middle of the stretch of a 10-story building. The SPSW (S4) model can be used as a model for application in a 10-story building, but the opening shape is changed to a rectangle like a window. From the modeling results using the SAP 2000 program, the profiles for HBE are WF 600.300 and VBE using KC 800.300, with a thickness of 4 mm infill plate and 12 mm stiffener plate. Control analysis of the model is also carried out such as mass participation control, structure vibration period control, dynamic shear force control of the structure, displacement control and cross section control that meet the requirements.